Toward elemental analysis of ambient single particles using electrodynamic balance and laser-induced breakdown spectroscopy. Issue 7 (2nd July 2020) - Heikkilä, Paavo; Rossi, Jussi; Rostedt, Antti; Huhtala, Janne; Järvinen, Anssi; Toivonen, Juha; Keskinen, Jorma
Abstract: In this article, we present a novel method for the elemental analysis of airborne aerosol particles using electrodynamic balance (EDB) trapping followed by laser-induced breakdown spectroscopy. The setup consists of a newly designed corona-based aerosol charger, double-ring electrodynamic balance trap and optical arrangement for the spectroscopy. Experimental laboratory measurements using the method show that the minimum particle size for successful analysis is 1 µm in diameter, and the minimum airborne concentration is of the order of 1 particle/cm 3 . In addition to the method, we will present results on the charging efficiency of the developed charger and novel stability analysis of the EDB at the charge region. The results from the stability analysis will ease the way toward analyzing submicron particles with the technique.